A Numerical Investigation on MHD Couple Heat and Mass Transfer Past a Rotating Vertical Cone Embedded in a Porous Medium - Veera Reddy, S.; S S Raju, G.; G. Vijaya Kumar, A. (International Journal of Engineering and Technology, 2018)
This collaborative effort highlights the effects of combined energy and species transmission through the both mechanism of convections of a fluid flow witch obeys Newton’s law of viscosity, over a rotatory upward directed geometrized cone from conic section surrounded with a medium possessing porosity along with applied magnetic field and chemical reaction effects with Dufour effect.  The fundamental laws such as mass conservative, linear momentum conservative, heat energy and molecular diffusion conservative field are transmuted using suitable  analogous variables witch do not change anyway the modelling and then shooting method that is implemented along with  Runge-Kutta method to obtain the solutions. The results obtained are in excellent agreement with previous works in the same discipline.  Graphical representation of with distinct numeral magnitudes for fluid transport, temperatures, species levels, besides that local polar tangential and azimuth (the angle between projected and reference vectors) coefficient of friction drag, local energy and mass transmission rates near the wall surface is displayed as one scrolls down and discussions for mixed values of some physical quantities independent of S.I units to gather much attention upon the results on the solutions are also made. Its applications include making equipment coolant, reactors with bedding, in a system of porous wafers absorbed by solar rays and in the preparation of some fusion materials. Other disciplinarians are aircrafts wings, space research, asteroid and geophysical matters, in concern of energy-species-density dependence.